2021
DOI: 10.1126/sciimmunol.abi4710
|View full text |Cite
|
Sign up to set email alerts
|

Assembly of a spatial circuit of T-bet–expressing T and B lymphocytes is required for antiviral humoral immunity

Abstract: Effective antiviral immunity requires generation of T and B lymphocytes expressing the transcription factor T-bet, a regulator of type 1 inflammatory responses. Using T-bet expression as an endogenous marker for cells participating in a type 1 response, we report coordinated interactions of T-bet–expressing T and B lymphocytes on the basis of their dynamic colocalization at the T cell zone and B follicle boundary (T-B boundary) and germinal centers (GCs) during lung influenza infection. We demonstrate that the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
38
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(43 citation statements)
references
References 77 publications
3
38
0
2
Order By: Relevance
“…Fate mapping studies have shown that a portion of ABCs are not GC-derived [ 28 ]. B cells outside of the GC express elevated phosphorylated signal transducer and activator of transcription 1 (pSTAT1), upstream of T-bet expression, in B cells [ 17 ], indicating that T-bet is likely up-regulated in B cells prior to GC entry [ 11 ]. It is possible, and has been previously suggested, that ABCs might undergo different differentiation processes and could arise from both within and outside of the GC [ 3 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Fate mapping studies have shown that a portion of ABCs are not GC-derived [ 28 ]. B cells outside of the GC express elevated phosphorylated signal transducer and activator of transcription 1 (pSTAT1), upstream of T-bet expression, in B cells [ 17 ], indicating that T-bet is likely up-regulated in B cells prior to GC entry [ 11 ]. It is possible, and has been previously suggested, that ABCs might undergo different differentiation processes and could arise from both within and outside of the GC [ 3 ].…”
Section: Introductionmentioning
confidence: 99%
“…IgG2a/c (IgG1 in humans) is associated with a Th1 response and is the major antiviral isotype [ 31 , 32 ]. Knocking out ABCs in mice leads to a significant decrease in IgG2a/c titers [ 11 13 ], and transfer of virus-specific antibodies into mice deficient in ABCs is able to partially restore control of chronic LCMV [ 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…Although both type 1 and type 2 immune stimuli drive Tfh cell development, the functional capacities of Tfh1 and Tfh2 cells are discrete. In turn, distinct Tfh cell function regulates the outcome of humoral immune responses and the host's immunity [13,18,20]…”
Section: Acute High-dose Helminth Infection Drives a Potent Tfh-gc Responsementioning
confidence: 99%
“…Although both type 1 and type 2 immune stimuli drive Tfh cell development, the functional capacities of Tfh1 and Tfh2 cells are discrete. In turn, distinct Tfh cell function regulates the outcome of humoral immune responses and the host's immunity [13,18,20]. The distinct functions of different subpopulations of Tfh cells suggest that they play key nonredundant roles in regulating immunity to a wide range of immune stimuli.…”
Section: Acute High-dose Helminth Infection Drives a Potent Tfh-gc Responsementioning
confidence: 99%
“…ABCs are elevated in the spleen and circulation during active viral infections and persist primarily in the spleen during chronic infection or upon infection resolution 7,8 . ABCs display multiple functional capacities including the secretion of antibodies and anti-viral cytokines, and activation of T cells 11,12 . T-bet expression in B cells is required for IgG2a/c class switching 13 and lack of ABCs exacerbates LCMV chronic infection in mice 14 .…”
Section: Introductionmentioning
confidence: 99%